DETERMINE THE EFFECT OF EDUCATION USING MEDIA LEAFLETS ON YOUNG WOMEN'S KNOWLEDGE ABOUT ANEMIA AT SMP NEGERI 2 PANGURURAN, SAMOSIR REGENCY IN 2023 - Sinaga, Lia Rosa Veronika; Pakpahan, Nita Ernawati; Manurung, Jasmen; Munthe, Seri Asnawati (TOUR HEALTH JOURNAL, 2023)
Background: Anemia in young women has a significant impacton the next phase of life. A decrease in productivity andachievement in learning is a short-term impact on adolescents(Nurrahman et al., 2021). Adolescent girls who experienceanemia have the risk of becoming anemic women of childbearingage, and subsequently becoming anemic pregnant women. Thiscondition will increase the risk of mothers giving birth to babieswith low birth weight (LBW), delivery complications and otherpregnancy risks. Babies born with LBW are a risk factor forstunting (Kemenkes RI, 2018).Purpose: This study aims to determine the effect of educationusing media leaflets on young women's knowledge about anemiaat SMP Negeri 2 Pangururan, Samosir Regency in 2023.Method: This type of research is a quasi-experimental withcontrol two group design pretest-posttest. The population andsample in this study were female adolescents at SMP Negeri 2Pangururan, Samosir Regency totaling 69 people.Results: The results of the study after the intervention weretested by Wilcoxon and obtained p = 0.000, which means thatthere is a significant effect on the level of knowledge aboutanemia between before and after being given the intervention.Disscusion and Conclusion: relationship between age, gender,This means that leaflets about anemia at SMP Negeri 2Pangururan, Samosir Regency have proven effective and havehad a positive impact in the form of increasing knowledge ofyoung women about anemia. This study recommends that leafletmedia in learning about anemia can be used as an innovation inincreasing the knowledge of young women about anemia so thatyoung women want to take iron tablets once a week to preventanemia.